PESAN DAKWAH MELALUI MUSIK ISLAMI - Muhammad Taufik; Noor Fadhli Marh (Tamaddun, 2018)
Da'wah is an obligation for everyone, especially someone who has been equipped with religious knowledge in depth, because the substance of the da'wah is to invite to the good and leave all forms of renunciation in a good way and and equipped with adequate knowledge, as well as its activities so that the message from The mission reaches the desired target. The development of the era marked by the fast flow of globalization can be felt by the people to all corners of this country. This causes us to have to rack my brain to develop strategies so that the preaching delivered can be accepted in a society that is very aware of worldly technology and modernization in various fields of life. Therefore, conventional propaganda activities tend to be less heard and sought after by the public today. In response to these problems it seems that Islamic music can be used as an effective means of da'wah today. We can assume that Islamic music is art, and art is beauty. By nature human beings are very fond of beauty, so it would be nice if preaching is delivered through media that is preferred by humans. In this study the authors collected data from various reference sources relating to Islamic da'wah and music that explained the relationship of Da'wah with Islamic music, the material and content delivered, the delivery strategy, the delivery ethics and other supporting matters, so that the propaganda activities through Islamic music can well realized and achieve the desired goals.